An optimisation framework for monitoring of SDN/OpenFlow networks. (2017) - Caraguay, Ángel Leonardo Valdivieso; Fernández, Jesús Antonio Puente; Villalba, Luis Javier García
The centralised control of the network and the separation of data and control planes proposed by software defined networking (SDN) have changed the rigid, static, and complex nature of the networks. The decisions taken by the control plane depends on the accuracy of the monitored information on network performance and detection of network events (link failure, delay, loss, network overhead). However, the monitoring information is typically provided by external network monitoring solutions which require the installation of specialised (and costly) equipment. This work proposes an efficient SDN monitoring framework using the OpenFlow protocol. Moreover, the pluggable architecture enables the creation, updating and customisation of high level metrics as well as the orchestrator balancing the monitoring tasks and offering an adaptive method of polling information requests. The implementation of network performance metrics and the results of experiments using video streaming traffic demonstrate the effectiveness of the framework.